How Having a Clear Why Can Help Us Cope With Almost Anything: Meaningful Well-Being and the COVID-19 Pandemic in México - Quiroga-Garza, Angelica; Cepeda-Lopez, Ana C.; Villarreal Zambrano, Sofía; Villalobos-Daniel, Victor E.; Carreno, David F.; Eisenbeck, Nikolett (Frontiers in Psychology, 2021)
Background: Coronavirus disease 2019 (COVID-19) has resulted in an increase in known risk factors for mental health problems. Mexico adopted lockdown and physical distancing as a containment strategy with potential consequences on day to day life, such as social isolation, loss of income and loneliness that can have important consequences in terms of mental health. Objective: We aimed to examine the effect of the initial phases of the COVID-19 pandemic on psychological distress, well-being and perceived physical health among Mexican-base respondents and to examine whether coping strategies would play a potential intermediating role in relation to these variables. Under the Existential Positive Psychology perspective, an emphasis was made on meaning-centered coping. Methods: A cross-sectional study was conducted between April 30 and June 16th 2020 among 604 Mexicans-base respondents of which 471 were women and 132 men. Data was collected by using online questionnaires. Psychological distress was measured using the Depression, Anxiety, and Stress Scale (DASS-21). The Brief COPE Inventory was used to assess problem-focused and emotion-focused coping strategies. We also used the Meaning-Centered Coping Scale (MCCS). PERMA-Profiler was used to assess well-being, perceived physical health, and loneliness. Profiler and Descriptive analyses and bivariate linear regression were performed to examine the association of variables. Results: 45.9% of the participants reported moderate to extremely severe psychological distress. Our results demonstrate that problem-focused and emotion-focused coping were positively related to psychological distress, whereas meaning-centered coping was negatively associated with distress. Furthermore, psychological distress played a potential negative role in the perceived physical health, while meaning-centered coping and well-being buffered the negative influence of psychological distress on perceived physical health (completely standardized indirect effect = –0.01, SE: 0.012, 95% CI [−0.065; −0.017]. Conclusion: Meaning-centered coping was found to suppress the negative influence of psychological distress on sensation of decreased physical health corroborating the critical role of meaning in life in promoting well-being. Future studies can further examine the value of the critical role of meaning in life in promoting well-being as a protective factor against severe distress during traumatic events. Findings of this study can be used to orient policies and interventions aimed to alleviate suffering in the midst of the COVID-19 pandemic.